Clinical and epidemiological performance of WHO Ebola case definitions: a systematic review and meta-analysis. Issue 11 (November 2020) - Caleo, Grazia; Theocharaki, Foivi; Lokuge, Kamalini; Weiss, Helen A; Inamdar, Leena; Grandesso, Francesco; Danis, Kostas; Pedalino, Biagio; Kobinger, Gary; Sprecher, Armand; Greig, Jane; Di Tanna, Gian Luca
Summary: Background: Ebola virus disease case definition is a crucial surveillance tool to detect suspected cases for referral and as a screening tool for clinicians to support admission and laboratory testing decisions at Ebola health facilities. We aimed to assess the performance of the WHO Ebola virus disease case definitions and other screening scores. Methods: In this systematic review and meta-analysis, we searched PubMed, Scopus, Embase, and Web of Science for studies published in English between June 13, 1978, and Jan 14, 2020. We included studies that estimated the sensitivity and specificity of WHO Ebola virus disease case definitions, clinical and epidemiological characteristics (symptoms at admission and contact history), and predictive risk scores against the reference standard (laboratory-confirmed Ebola virus disease). Summary estimates of sensitivity and specificity were calculated using bivariate and hierarchical summary receiver operating characteristic (when four or more studies provided data) or random-effects meta-analysis (fewer than four studies provided data). Findings: We identified 2493 publications, of which 14 studies from four countries (Sierra Leone, Guinea, Liberia, and Angola) were included in the analysis. 12 021 people with suspected disease were included, of whom 4874 were confirmed as positive for Ebola virus infection. Six studies explored the performance of WHO case definitions in non-paediatric populations, and in all of these studies, suspected and probable cases were combined and could not be disaggregated for analysis. The pooled sensitivity of the WHO Ebola virus disease case definitions from these studies was 81·5% (95% CI 74·1–87·2) and pooled specificity was 35·7% (28·5–43·6). History of contact or epidemiological link was a key predictor for the WHO case definitions (seven studies) and for risk scores (six studies). The most sensitive symptom was intense fatigue (79·0% [95% CI 74·4–83·0]), assessed in seven studies, and the least sensitive symptom was pain behind the eyes (1·0% [0·0–7·0]), assessed in three studies. The performance of fever as a symptom varied depending on the cutoff used to define fever. Interpretation: WHO Ebola virus disease case definitions perform suboptimally to identify cases at both community level and during triage at Ebola health facilities. Inclusion of intense fatigue as a key symptom and contact history could improve the performance of case definitions, but implementation of these changes will require effective collaboration with, and trust of, affected communities. Funding: Médecins sans Frontières.